The Dissenting Interpretation of the Term “Immovable Property” in the Treaty of 1964 between Belgium and France and the Outcome of the Discussion in Their New Treaty - Docclo, Caroline (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
This contribution illustrates the inability of the Belgian and French authorities and courts to agree on the interpretation the term “immovable property” (bien immobilier) used in the double tax treaty of 10 March 1964 between Belgium and France when characterizing shares in French real estate companies for the purposes of distributing the power to tax dividends or capital gains derived from those shares.